1983
DOI: 10.1017/s0021932000014413
|View full text |Cite
|
Sign up to set email alerts
|

Family Break-Down and Stress in Huntington's Chorea

Abstract: The incidence of family breakdown and stress has been examined in an unselected group of 92 South Wales families, each containing a patient suffering from Huntington's chorea, and related to the onset and duration of the disease, age of the patient, and behavioural symptoms shown. The frequency of actual and attempted suicide is analysed and the effects of the disorder on the primary care agent for the patient discussed. Some of the effects on children and the needs of the families for support and practical he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…This study raises a number of issues that genetics professionals may want to consider when working with families who are affected by HD. First, previous research has highlighted the potentially traumatic experience for children and YP who grow up in a family with HD (5), and this was an important theme. At particular risk were YP who lived alone with an affected parent whose symptoms were increasingly unmanageable, or who was emotionally unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study raises a number of issues that genetics professionals may want to consider when working with families who are affected by HD. First, previous research has highlighted the potentially traumatic experience for children and YP who grow up in a family with HD (5), and this was an important theme. At particular risk were YP who lived alone with an affected parent whose symptoms were increasingly unmanageable, or who was emotionally unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…family break‐up, embarrassment at taking friends home. Consequently, some YP may experience considerable social isolation (5, 12), which may also be compounded by a fear of alerting professionals (14). In contrast, more recent research highlights the considerable resilience of YP in families affected by HD, and in relation to predictive testing YP have demonstrated a capacity for decision making beyond what would be expected of their age group (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that these informal carers frequently subordinate their own needs and quality of life to the needs of their loved ones [18,19]. Moreover, stress and anxiety are common and emanate from their caregiving role [20][21][22][23]. In addition, the symptoms and genetic nature of HD makes this carer role distinct from others [24].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…In addition, over time the spouse takes on an increasing nursing role, which creates a psychological distance between the patient and his/her spouse [22]. HD greatly impacts the patients’ physical and psychosocial well-being [25, 26], and places a heavy burden on families [2729]. Interestingly, some research has indicated that there is a discrepancy between the aspects of HD the patient finds most disturbing and those the spouse or partner finds most disturbing.…”
mentioning
confidence: 99%